2006
DOI: 10.1093/annonc/mdj131
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib (VELCADE®) in metastatic breast cancer: pharmacodynamics, biological effects, and prediction of clinical benefits

Abstract: Bortezomib was well tolerated but showed limited clinical activity against metastatic breast cancer when used as a single agent. The future development of this agent for the treatment of breast cancer should be guided by in vivo models that optimize activity in combination with other antitumor agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 17 publications
6
97
0
Order By: Relevance
“…It is the first of a novel class of anticancer drugs, known as proteasome inhibitors, to be approved for clinical use. Since its discovery, bortezomib has been used to treat a variety of human tumors, such as multiple myeloma (3)(4)(5)(6)(7)(8), lymphoma (9,10), non-small cell lung cancer (11,12), renal cancer (13,14), prostate cancer (15)(16)(17), pancreatic cancer (18), melanoma (19), breast cancer (20,21), and ovarian cancer (22). Bortezomib inhibits a key regulator of intracellular protein degradation, the 26S proteasome, which has the downstream effect of inducing apoptotic cancer cell death by means of multiple mechanisms.…”
mentioning
confidence: 99%
“…It is the first of a novel class of anticancer drugs, known as proteasome inhibitors, to be approved for clinical use. Since its discovery, bortezomib has been used to treat a variety of human tumors, such as multiple myeloma (3)(4)(5)(6)(7)(8), lymphoma (9,10), non-small cell lung cancer (11,12), renal cancer (13,14), prostate cancer (15)(16)(17), pancreatic cancer (18), melanoma (19), breast cancer (20,21), and ovarian cancer (22). Bortezomib inhibits a key regulator of intracellular protein degradation, the 26S proteasome, which has the downstream effect of inducing apoptotic cancer cell death by means of multiple mechanisms.…”
mentioning
confidence: 99%
“…Two previous phase II studies with single agent bortezomib in metastatic breast cancer have only reported disease stabilisation. Yang et al (32) reported on a phase II study with bortezomib using a biweekly regimen of 1.5 mg/m 2 followed by one week rest every 21 days in 12 patients, all suffering from measurable metastatic breast cancer. One (8.3%) of these 12 patients experienced stable disease for up to 5 cycles of 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PS-341 exhibits a wide range of antitumor activity and increases the activity of multiple chemotherapeutic agents (5,6,22,23). Although PS-341 was found to be active against breast cancer cell lines, in vivo models and phase Ⅰ clinical trials have found it ineffective for breast cancer when used as a single agent (24), and limited efficacy of PS-341 has been noted in combination with several chemotherapeutic agents (25,26).…”
Section: Discussionmentioning
confidence: 99%